The North-East as Gateway to South-East Asia: Big Dream and Home Truths. - Sarma, Atul (2006)
India’s ‘Look East policy’ has led to a vision for the North-East: a gateway to South-East Asia. It has spurred a good deal of optimism about the possible gains to the region. It is in this context that the paper addresses questions such as: How does market integration work? What do we learn from the internationalization of the Assam economy in the past? How have formal and informal trade flows with the South-East Asia in the recent past impacted the North-East economies? What are the required enablingpolicy environment and physical infrastructure for trade linkage to yield gains? What initiatives should the North-East take to maximize the economic gains as and when the vision of its integration with the South-East Asia becomes a reality?